2006
DOI: 10.1159/000097259
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of T Cell Responses in HTLV-1 Carriers and in Patients with Myelopathy Associated with HTLV-1

Abstract: Objective: Human T lymphotropic virus-type 1 (HTLV-1) activates the immune system leading to a persistent and exacerbated T-cell response with increased production of IFN-γ and TNF-α. Overproduction of pro-inflammatory cytokines is correlated with the development of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), although some HTLV-1 carriers also show high levels of these cytokines. In this study, the ability of regulatory cytokines and cytokine antagonists to inhibit spontaneous IFN-γ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 56 publications
(34 reference statements)
1
24
0
Order By: Relevance
“…We have previously shown that IL-10, anti-IL-2 and anti-IL-15 down-modulate IFN-g production in HTLV-1 carriers but do not suppress IFN-g synthesis in HAM/TSP [25]. In this study we evaluated whether the exogenous addition of IL-10 and neutralization of IL-2 and IL-15 was able to downmodulate IFN-g synthesis in cell cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that IL-10, anti-IL-2 and anti-IL-15 down-modulate IFN-g production in HTLV-1 carriers but do not suppress IFN-g synthesis in HAM/TSP [25]. In this study we evaluated whether the exogenous addition of IL-10 and neutralization of IL-2 and IL-15 was able to downmodulate IFN-g synthesis in cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that while PBMCs from HTLV-1 carriers can be modulated when IL-10 and anti-IL-2 are added in vitro, cells from HAM/TSP patients exhibit poor modulation of the immune response [25]. To evaluate the ability of IL-10 to decrease the spontaneous IFN-g production observed in HTLV-1-infected patients, PBMCs of IDH patients and HTLV-1 carriers were cultured in the presence of IL-10.…”
Section: Down-regulation Of Ifn-g Production By Cytokine and Anti-cytmentioning
confidence: 99%
“…Recently, the inability of the recombinant human IL-10 in downmodulating IFN-γ production in vitro in HAM/TSP individuals was described [22]. However, the low ratio of IFN-γ/IL-10 induced by some Schistosoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HTLV-1 infection may influence the immune response to other pathogens, increasing susceptibility and modifying the clinical manifestation of strongyloidiasis (4,5), tuberculosis (6,7), schistosomiasis (8), and scabies (9). The pathology related to HTLV-1 infection is associated with an exaggerated and inappropriately modulated immune response, and a high proviral load (10). The mechanisms related to the ability of HTLV-1 to increase susceptibility or influence the clinical course of other diseases are not fully understood.…”
Section: Introductionmentioning
confidence: 99%